BIOACCUMULATION OF HEAVY METALS BY BACILLUS MEGATERIUM FROM PHOSPHOGYPSUM WASTE - IOANA ADRIANA STEFANESCU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The aim of present study was to characterize the bioaccumulation capacity of heavy metals by Bacillus megaterium from phosphogypsum waste. The Bacillus megaterium strain (BM30) was isolated from soil near the phosphogypsum (PG) dump. For the bioaccumulation quantification produced by BM30 strain were used three experimental treatments respectively with 2, 6 and 10 gL-1 PG. Cellular biomass samples were collected punctually at ages corresponding to the three stages of the development cycle of the microorganism: exponential phase, stationary phase and decline phase and the heavy metals concentrations were measured by atomic absorption spectroscopy. The bioaccumulation yields in cell biomass, relative to the total amount of analyte introduced in the reaction medium were between 20 - 80 %, the lowest value was recorded by Cu and highest by Mn. The study results indicated that the isolated strain near the dump PG, BM30, bioaccumulate heavy metals monitored in cell biomass in the order Cu > Fe > Zn = Mn.